The efficacy of the self-adjusting file and ProTaper for removal of calcium hydroxide from root canals - Faria, Gisele [UNESP]; Kuga, Milton Carlos [UNESP]; Ruy, Alessandra Camila [UNESP]; Aranda-Garcia, Arturo Javier; Bonettifilho, Idomeo [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Leonardo, Renato de Toledo [UNESP] (My University, 2013)
Objective: The goal of this study was to evaluate the efficacy of the Self-Adjusting File (SAF) and ProTaper for removing calcium hydroxide [Ca(OH)2] from root canals. Material And Methods: Thirty-six human mandibular incisors were instrumented with the ProTaper system up to instrument F2 and filled with a Ca(OH)2-based dressing. After 7 days, specimens were distributed in two groups (n=15) according to the method of Ca(OH)2 removal. Group I (SAF) was irrigated with 5 mL of NaOCl and SAF was used for 30 seconds under constant irrigation with 5 mL of NaOCl using the Vatea irrigation device, followed by irrigation with 3 mL of EDTA and 5 mL of NaOCl. Group II (ProTaper) was irrigated with 5 mL of NaOCl, the F2 instrument was used for 30 seconds, followed by irrigation with 5 mL of NaOCl, 3 mL of EDTA, and 5 mL of NaOCl. In 3 teeth Ca(OH)2 was not removed (positive control) and in 3 teeth canals were not filled with Ca(OH)2 (negative control). Teeth were sectioned and prepared for the scanning electron microscopy. The amounts of residual Ca(OH)2 were evaluated in the middle and apical thirds using a 5-score system. Results: None of the techniques completely removed the Ca(OH)2 dressing. No difference was observed between SAF and ProTaper in removing Ca(OH)2 in the middle (P=0.11) and the apical (P=0.23) thirds. Conclusion: The SAF system showed similar efficacy to rotary instrument for removal of Ca(OH)2 from mandibular incisor root canals.
Keywords: Calcium hydroxide; Endodontics; Irrigation; Root canal therapy